2017
DOI: 10.5430/ijdi.v4n2p47
|View full text |Cite
|
Sign up to set email alerts
|

Sex dependent variations in craniofacial soft-tissue thicknesses estimated from MRI and CT scans: A pilot study based on Northwest Indian subjects

Abstract: Craniofacial identification is a technique for prediction and recreation of life-like appearances of an individual, recreated onto an unknown skull on the basis of intricate relationship existing between underlying bony contour and the overlying soft tissues, muscles and skin. Tissue thicknesses in different population have wide variations due to disparities in nutritional, environmental or genetical factors. The physical health, nutritional status and disease activity of an individual have significant and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 26 publications
0
20
1
1
Order By: Relevance
“…In spite of lateral cephalograms clearly demonstrating the profile soft tissue outlines and facilitating midline measurements, the accuracy of 2D radiographic techniques is limited when compared to the advanced imaging owing to technique related errors such as superimposition. On the contrary, the differences between CT[ 30 ] and CBCT (current study) derived values are negligible and statistically insignificant at majority of the landmarks. CBCT provides high-quality images at a lower radiation dose using less expensive equipment.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In spite of lateral cephalograms clearly demonstrating the profile soft tissue outlines and facilitating midline measurements, the accuracy of 2D radiographic techniques is limited when compared to the advanced imaging owing to technique related errors such as superimposition. On the contrary, the differences between CT[ 30 ] and CBCT (current study) derived values are negligible and statistically insignificant at majority of the landmarks. CBCT provides high-quality images at a lower radiation dose using less expensive equipment.…”
Section: Discussioncontrasting
confidence: 52%
“…To understand whether the choice of technique affects the measurements, the data of the current study were compared with three other Indian studies[ 17 18 30 ] wherein the researchers have used various noninvasive techniques such as lateral cephalogram,[ 17 ] MRI[ 18 ] and CT.[ 30 ] The midline FSTT values of all the four studies differed from one another, the differences being statistically significant between the radiographic study[ 17 ] and all the other three. In spite of lateral cephalograms clearly demonstrating the profile soft tissue outlines and facilitating midline measurements, the accuracy of 2D radiographic techniques is limited when compared to the advanced imaging owing to technique related errors such as superimposition.…”
Section: Discussionmentioning
confidence: 99%
“…Because it may never be possible to describe and predict all the variations of the male and female human face and the relationship between the bone and soft tissue, the measurement of FSTT has multiple diagnostic, clinical, anthropological, and forensic applications, including craniofacial reconstruction, facial plastic surgery, reconstructive and orthognathic maxillofacial surgery, and evaluation of benign and malignant facial tumors [ 18 ]. Because soft tissues do not form a layer of equal thickness which simply shapes the configuration of basic dental and skeletal structures, the variability of FSTT can reflect the facial profile and should be a factor in diagnosis and the planning of orthodontic treatment [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that not all areas of the soft tissue profile directly follow skeletal structures and, in some areas the contours of the facial tissue deviate from basic skeletal structures [ 7 , 18 , 34 ]. In everyday orthodontic practice, there are standard cephalometric measurements and analysis done on the basis of cephalometric radiography of facial profiles to determine relationships between contours of a facial skeleton, as well as FSTT measurements [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation